Literature Study: Review of the Negative Impacts of Mining Activities in Various Countries on the Environment, Society, and Local Economies, and Mitigation Strategies - Samosir, Angela Glorya Marito; Sutisna, Sobar; Prakoso, Lukman Yudho (Golden Ratio of Data in Summary, 2025)
Mining activities, on the one hand, contribute significantly to national development. However, these activities negatively impact the environment, society, and economy, particularly for local communities. This literature review aims to examine the negative impacts of mining activities in various countries on the environment, society, and economy, as well as the mitigation strategies employed to reduce these negative impacts. The method used in this study is a literature review, analyzing international journal articles published between 2020 and 2024, with a total of 24 journals analyzed, consisting of 7 journals from 2020, 4 journals from 2021, 4 journals from 2022, 4 journals from 2023, and 5 journals from 2024 discussing the negative impacts of mining activities and mitigation strategies implemented to reduce these impacts. The results of the study indicate that the environmental impacts of mining include soil degradation, water pollution, and ecosystem damage. The social impacts include forced migration and social tension, while the economic impacts include economic instability and unequal distribution of economic benefits. The mitigation strategies identified are that to reduce the negative impacts of mining, it is necessary to conduct environmental impact assessments, rehabilitate mining areas, adopt environmentally friendly technologies, and implement more comprehensive policies that involve local communities in decision-making.